The White-Centering Logic of Diversity Ideology. (November 2019) - Mayorga-Gallo, Sarah
In this article, I present a framework for diversity as a racial ideology that rearticulates the logic of civil rights. Diversity ideology is, in part, a co-optation of calls for race consciousness that challenged color blindness: it highlights race and other axes of difference to achieve a color-blind ideal of fairness where race will no longer matter. In this way, diversity ideology creates space for minor acknowledgment of structural inequality in the abstract. This is an important difference from color-blind racism, which explains inequality as a function of the past, individual "racist" bad apples, or the failings of people of color. The logic of diversity ideology is based on four tenets (diversity as acceptance, diversity as intent, diversity as commodity, and diversity as liability) that frame an amorphous diversity as the answer to racial inequality, while centering white people's desires and feelings. These conceptualizations of diversity are devoid of power and history, which is how systemic whiteness is reinscribed.